An Analysis of Learning Styles on Renewable Energy Material in Independent Curriculum for Differentiation Learning - Rolipa Rolipa; Ketang Wiyono; Sudirman Sudirman; Apit Fathurohman; Leni Marliana (Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to analyze the effectiveness of student learning styles on renewable energy material in the independent curriculum for differentiation. This research is a qualitative descriptive study. The method used was a learning style survey in the form of a questionnaire developed by Chislett and Chapman, which was conducted on 30 students in class X.4 of SMA Negeri 3 Banyuasin III. The results of the learning style survey were then analyzed and grouped by researchers according to the characteristics of learning styles, namely 50% visual learning style, 30% audio learning style, and 20% kinesthetic learning style. These results indicate that the tendency of students' learning styles varies in one class. Furthermore, a pretest and posttest assessment of renewable energy material was held for students. As for the results of the analysis of pretest, posttest, and gain learning outcomes, the average obtained by visual students was 19.3, audio 22.6, and kinesthetic 23.3 for posttest visual learning styles (77.0, audio 78.3, and kinesthetic 81.0), and visual gain was 57.7, audio 55.7, and kinesthetic 57.6. N-gain was analyzed to see the increase in learning outcomes, which obtained results for an average visual learning style of 0.71, audio 0.72, and kinesthetic 0.75. From this analysis, it can be concluded that differentiated learning with the learning style of renewable energy material can increase the number of students learning in the high category.